KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA MAHOTTAMA DALAM PELAYANAN PENYEDIAAN AIR BERSIH DI KECAMATAN NUSA PENIDA - Putra Mursidi, I Kadek Unggara; Yudharta, I Putu Dharmanu; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2021)
PDAM Tirta Mahottama Klungkung Regency is one of the regional companies that is engaged in providing clean water to the community with the aim of improving community welfare which includes social, health and public service aspects. The purpose of this research is to analyze, find out, and describe in depth the performance of the PDAM Tirta Mahottama at Nusa Penida District, Klungkung Regency. Based on a study using Dwiyanto's theory of performance, the results of the research show that several indicators have gone well, namely accountability, while indicators of productivity, service quality, responsiveness and responsibility have been running quite well, but are still not optimal because there are inhibiting factors such as geographical conditions. , company financing is still limited from the APBD related to company developments, technical operations are still lacking and water production capacity is still low. Keywords: Performance, PDAM, Clean Water Supply Services